The influence of bond-coating on plasma sprayed alumina-titania, doped with biologically derived hydroxyapatite, on stainless steel - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2008)
The influence of bond-coating on the quality of thin coatings (similar to 100 mu m) of alumina-titania (60%-40%), doped with 5% and 10% bovine hydroxyapatite, plasma-spayed on stainless steel (316), was experimentally investigated by measuring the tensile strength and the ratio of adhesive/cohesive strength of the coatings. The bond-coating layer was alumina-titania (60%-40%). The experimental results (mainly the values of the ratio adhesive/cohesive strength and the microstructure of the coating layers) and their discussion in the light of earlier similar studies show that bond-coating process can result in coating composite structures of high quality, which is of high importance for devices used in biomedicine.
Keywords: MECHANICAL-PROPERTIES